Multi-institutional comparison of secondary check of treatment planning using computer-based independent dose calculation for non-C-arm linear accelerators. (December 2018) - Tachibana, Hidenobu; Uchida, Yukihiro; Miyakawa, Ryuta; Yamashita, Mikiko; Sato, Aya; Kito, Satoshi; Maruyama, Daiki; Noda, Shigetoshi; Kojima, Toru; Fukuma, Hiroshi; Shirata, Ryosuke; Okamoto, Hiroyuki; et al.
Highlights: This is the first multicenter study of secondary plan checks for non-C-arm linacs. A total of 973 CyberKnife, Vero4DRT, and TomoTherapy treatment plans were assessed. A 5% difference in the check is feasible as an action level for non-C-arm linacs. A 3–4% systematic difference in the check is apparent in heterogeneous conditions. Abstract: Purpose: This report covers the first multi-institutional study of independent monitor unit (MU)/dose calculation verification for the CyberKnife, Vero4DRT, and TomoTherapy radiotherapy delivery systems. Methods: A total of 973 clinical treatment plans were collected from 12 institutions. Commercial software employing the Clarkson algorithm was used for verification after a measurement validation study, and the doses from the treatment planning systems (TPSs) and verification programs were compared on the basis of the mean value ± two standard deviations. The impact of heterogeneous conditions was assessed in two types of sites: non-lung and lung. Results: The dose difference for all locations was 0.5 ± 7.2%. There was a statistically significant difference (P < 0.01) in dose difference between non-lung (−0.3 ± 4.4%) and lung sites (3.5 ± 6.7%). Inter-institutional comparisons showed that various systematic differences were associated with the proportion of different treatment sites and heterogeneity correction. Conclusions: This multi-institutional comparison should help to determine the departmental action levels for CyberKnife, Vero4DRT, and TomoTherapy, as patient populations and treatment sites may vary between the modalities. An action level of ±5% could be considered for intensity-modulated radiation therapy (IMRT), non-IMRT, and volumetric modulated arc radiotherapy using these modalities in homogenous and heterogeneous conditions with a large treatment field applied to a large region of homogeneous media. There were larger systematic differences in heterogeneous conditions with a small treatment field because of differences in heterogeneity correction with the different dose calculation algorithms of the primary TPS and verification program.